2009
DOI: 10.1038/oby.2009.3
|View full text |Cite
|
Sign up to set email alerts
|

Visceral and Subcutaneous Adiposity and Adiponectin in Middle‐aged Japanese Men: The ERA JUMP Study

Abstract: Adiponectin is reduced in obesity and has been suggested to play an important role in modulation of atherosclerosis. We studied the relationship between visceral (VAT) and subcutaneous (SAT) adipose tissue and serum adiponectin concentrations in Japanese men. Participants were 304 randomly selected community‐based Japanese men aged 40–49 without a prior history of cardiovascular disease. Participants were grouped according to tertiles of serum adiponectin. In multiple linear regression analysis including age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
6
27
0
Order By: Relevance
“…Although 35,23, and 17% of smokers in the normalweight, overweight, and obese categories, respectively, had spirometry-defined COPD, the remainder was considered at risk for COPD. Of the 417 subjects with COPD overall, 175 subjects were in GOLD stage 1, 211 subjects were in GOLD stage 2, and 31subjects were in GOLD stage 3 disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 35,23, and 17% of smokers in the normalweight, overweight, and obese categories, respectively, had spirometry-defined COPD, the remainder was considered at risk for COPD. Of the 417 subjects with COPD overall, 175 subjects were in GOLD stage 1, 211 subjects were in GOLD stage 2, and 31subjects were in GOLD stage 3 disease.…”
Section: Resultsmentioning
confidence: 99%
“…Smokers develop chronic bronchitis and/or emphysema, but these two traditional phenotypes of COPD are not always easily distinguishable (35). Although obesity is typically described as seen with chronic bronchitis, emphysema is typically associated with a low BMI value (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, results from previous studies in Asian populations suggest that intra-abdominal fat may reduce adiponectin levels to a greater extent than subcutaneous fat, 19--21 although other studies did not support this. 22,23 Previous studies on ethnic differences in insulin resistance mainly compared various ethnic groups with whites who have consistently been observed to have the lowest level of insulin resistance among major ethnic groups for a given degree of adiposity. 24--26 Among the few studies that included multiple Asian ethnic groups, two Canadian studies 3,27 found higher insulin resistance in Asian Indians than in Chinese, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, accumulation of visceral fat is associated with hypoadiponectinemia (Nakamura et al, 2009), indicating that the synthesis of adiponectin is impaired in obese individuals. Accordingly, adiponectin production by adipocytes is inhibited by pro-inflammatory factors, such as TNF-α, IL-6, and IL-1β, as well as by hypoxia and oxidative stress (Ouchi et al, 2003;Berg, Scherer, 2005;Deng, Scherer, 2011).…”
Section: Adiponectinmentioning
confidence: 99%